Burial System in Karakelang Island, Talaud Regency, North Sulawesi - Ipak Fahriani; Vivi Sandra Sari (Badan Riset dan Inovasi Nasional, 2023)
Karakelang is an island which administratively located in Talaud Islands Regency, North Sulawesi. As one of the migration entrances of immigrants from the north of Indonesia islands, Talaud has become a quite wide area of prehistorical findings site dispersion and various activities that occurred in Talaud that provide the proof of civilization. One of the civilization heritages is burial system. This writing aims to explore the burial system in Karakelang Island in the past by looking at the site dispersion potential of occupancy area. The data were collected through survey and excavation. The research result shows that the collected occupancy sites in Karakelang reflect the burial activities in this area. The dispersion of occupancy site and burial system in Karakelang Island were parts of adaptation system of the people in Karakelang Island. It was mostly influenced by the natural resources that closely related to the developed local culture in Talaud.